Collaborative Governance dan Pengelolaan Lingkungan Hidup di Kawasan Pertambangan - Amelia Novita, Asti (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
This paper examines the role of collaborative governance to improve environmental governance in ensuring environmental security, particularly in the mining areas. The extractive industry has been always in the spotlight in its relation with the environmental security issues. Until today, the mining companies are still counted as a pawn for environmental sustainability efforts. In accordance with the sustainable development goal, environmental management practices could not be imposed to one actor only. Collaborative governance approach emerged as an alternative solution in answering these demands.